Synergistic Activity of Fluoroquinolones Combining with Artesunate Against Multidrug-Resistant Escherichia coli - Wei, SiMin (Microb Drug Resist, 2020)
Multidrug resistance (MDR) is an increasing public health concern worldwide. Artesunate (ART) has been reported to be significantly effective in enhancing the effectiveness of various β-lactam antibiotics against MDR Escherichia coli via inhibiting the efflux pump genes. Apart from β-lactam antibiotics, there is no report regarding the potential synergistic effects of ART combining with fluoroquinolones (FQs). In this study, we investigated whether ART can enhance the antibacterial effects of FQs in vitro. The antibacterial activity of ART and antibiotics against 13 animal-derived E. coli clinical isolates was assessed for screening MDR strains. Then the synergistic activity of FQs with ART against MDR E. coli isolates was evaluated. Daunorubicin (DNR) accumulation within E. coli and messenger RNA (mRNA) expressions of acrA, acrB, tolC, and qnr genes were investigated. The results showed that ART did not show significant antimicrobial activity. However, a dramatically synergistic activity of ART combining with FQs was obsessed with (ΣFIC) = 0.12–0.33. ART increased the DNR accumulation and reduced acrAB-tolC mRNA expression, but enhanced the mRNA expression of qnrS and qnrB within MDR E. coli isolates. These findings suggest that ART can potentiate FQs activity which may be associated with drug accumulation by inhibiting the expression of acrAB-tolC.